The Role of Career Adaptability, the Tendency to Consider Systemic Challenges to Attain a Sustainable Development, and Hope to Improve Investments in Higher Education - Di Maggio, Ilaria; Ginevra, Maria Cristina; Santilli, Sara; Nota, Laura; Soresi, Salvatore (Frontiers in Psychology, 2020)
Based on the life design paradigm and career construction adaptation model and on recent directions from the perspective of sustainable and inclusive career guidance, the study aimed at examining the relationship between career adaptability, the tendency to consider systemic challenges to attain sustainable development, and state personal and social hope and their role on the tendency to invest in higher education. The analyses carried out involving 416 Italian high school students found that career adaptability and the tendency to consider systemic challenges in order to attain sustainable development were directly and indirectly, through state personal and social hope, related to the tendency to invest in higher education. The results obtained allowed to provide new contributions to extend results previously described by the life design approach in career development issues and provided useful suggestions for preventive career interventions.